The prevalence of violence directed at paramedic services personnel - Gabrovec, Branko (Obzornik zdravstvene nege, 2015)
Introduction: Providers of health care are frequently subject to violence. The purpose of this research is to identify the type of violence suffered by first responders and the frequency of violence, since there is a lack of research in this area. Methods: A non-experimental sampling research method was used for this research; the research instrument is a structured questionnaire. We invited 36 rescue stations in Slovenia to participate, and 29 responded to the request; 246 questionnaires (68.3 %) were returned out of a total of 360. Data were analysed by means of descriptive statistics, correlation, the Kolmogorov-Smirnov test, Pearson's chi-square test, Mann-Whitney U test and linear regression with a significance of p < 0.05. Results: Seventy-eight per cent of respondents reported they had been verbally abused by their patients in the reporting year, while 49.6 % respondents reported they had been physically abused and 26.8 % of all respondents suffered injuries inflicted by patients. In the reporting year, 24.4 % of respondents experienced sexual harassment. A correlation was established between facing and experiencing fear (p = 0.017), between physical violence and feelings of vulnerability (p = 0.005), and between experiencing physical violence by the patient and lack of knowledge of how to manage patients' aggression (p = 0.012). Discussion and conclusion: The research could serve as a basis for a comprehensive approach to aggression management for nursing care professionals in paramedic services.
Keywords: nursing; paramedic; reševalci; safety; security; varnost; zdravstvena nega